160k views
0 votes
If f(x)=3x^2+1 and g(x)=1-x, what is the value of (f-g)(2)?

User Diboliya
by
5.1k points

2 Answers

2 votes

Answer:


(f-g)(2)=28

Explanation:

Given:


f(x)=3x^2+1


g(x)= 1-x

To find the equivalent expression of
(f-g)(2).


(f-g)(2) = f(2) - g(2)

Find g(x)


g(x)=1-x

Sub x for 2


g(2)=1-2


g(2)=-1

Find f(x)


f(x)=3x^2+1

Sub x for 2


f(2)=3(2)^2+1


f(2)=12+1


f(2)=12+1


f(2)=13

Solve for the giving value


(f-g)(2)


(13- (-1)) (2)


14(2)

28

User Ben Simmons
by
4.8k points
3 votes

The answer should be 14.

You just have to substitute x with the given number and finish the equation.

User Rodrigo Elias
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.